THE EFFECT OF PROFESSIONAL SKEPTICISM, EXPERTISE, AUDIT FEE, AND AUDIT RISK ON AUDITOR’S OPINION WITH CLIENT PREFERENCE AS MODERATOR - Betri Sirajuddin; Thalia Purwita Anggraini (Asosiasi Fakultas Ekonomi dan Bisnis Perguruan Tinggi Muhammadiyah, 2019)
The purposes of this study are to determine the effect of professional skepticism, expertise, audit fee, audit risk on the auditor’s opinion, and to determine preference client as the moderating variable on the effect of professional skepticism, expertise, audit fee, and audit risk on the auditor’s opinion. It is an empirical study on the public accountant firms and the Audit Board of the Republic of Indonesia (BPK RI) Representative Office in Palembang, South Sumatra, Indonesia. This study developed associative hypotheses and tested them. The data consisted of primary data and secondary data. The population of this research was the auditors of public accountant firms and BPK RI in Palembang. Totally, 111 respondents were involved. The techniques used for collecting the data were in-depth interviews, questionnaires, and documentation. The techniques used for analyzing the data were quantitative analysis and qualitative analysis. This study indicates that professional skepticism insignificantly affects the auditor’s opinion, expertise significantly affects the auditor’s opinion, audit fee significantly affects the auditor’s opinion, and audit risk significantly affects the auditor’s opinion. Furthermore, there is no significant relationship on the auditor’s opinion from the interaction between the client preference and professional skepticism and expertise. Meanwhile, client preference is a quasi-moderator on the influence of audit fee and audit risk on the auditor’s opinion.